52.2k views
3 votes
6(x-4)=24x show your work

User Aurelin
by
4.9k points

2 Answers

4 votes

Answer:

x=-4/3

Explanation:

6x-24=24x

6x=24x+24

6x-24x=24

-18x=24

x= -4/3

User Markus Proske
by
4.9k points
2 votes

Answer:

x = -4/3

Explanation:

1. Distribute

6(x - 4) = 24x

6x - 24 = 24x

2. Add 24 to both sides of equation

3. Simplify

4. Subtract 24x from both sides of the equation

5. Simplify

6. Divide both sides of the equation by the same term

7. Simplify

hope it helped

User Jtooker
by
4.5k points